Dialogické a monologické žánry mluvených projevů - Müllerová, Olga (Stylistyka, 2000)
The author gives an overview of elementary types (genres’) ofspoken texts, monologi[1]cal as well as dialogical, and an attempt at a linguistic characterization of all of them with short examples. The transcripts are part of a text corpus that includes tape record[1]ings from six different regions of Bohemia and Moravia.